Teaching in the Belo Horizonte public school system: analysis of academic production - Adriana Duarte (Universidade Federal de Santa Catarina, 2008)
This article analyzes studies about teaching undertaken by masters students who studied municipal schools in Belo Horizonte, from 1986-2006. Nine master's dissertations were found in this period, in five subthemes. Analysis of these dissertations observed the research question/object of study; the epistemological focus; the key categories used; the methodological option; the scope of the study and the principal conclusions. The article relates the studies conducted for the dissertations with theoretical studies about research and teaching.